2020
DOI: 10.1186/s13054-020-03265-y
|View full text |Cite
|
Sign up to set email alerts
|

(1,3)-β-d-Glucan-based empirical antifungal interruption in suspected invasive candidiasis: a randomized trial

Abstract: Background (1,3)-β-d-Glucan has been widely used in clinical practice for the diagnosis of invasive Candida infections. However, such serum biomarker showed potential to guide antimicrobial therapy in order to reduce the duration of empirical antifungal treatment in critically ill septic patients with suspected invasive candidiasis. Methods This was a single-centre, randomized, open-label clinical trial in which critically ill patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…Further investigation during the follow-up showed 29.7% of the false negative results were due to insu cient increase compared to the threshold, and 14.8% were due to the lag in increase. Some studies previously suggested to use the negative results of BDG to exclude IC diagnosis and allow discontinuation of the empirical therapy [30,33,34]. However, this might delay the preemptive therapy as BDG in this study reacted slowly (averagely 3 days later) and rose insu ciently, which might cause falsenegativity.…”
Section: Discussionmentioning
confidence: 74%
“…Further investigation during the follow-up showed 29.7% of the false negative results were due to insu cient increase compared to the threshold, and 14.8% were due to the lag in increase. Some studies previously suggested to use the negative results of BDG to exclude IC diagnosis and allow discontinuation of the empirical therapy [30,33,34]. However, this might delay the preemptive therapy as BDG in this study reacted slowly (averagely 3 days later) and rose insu ciently, which might cause falsenegativity.…”
Section: Discussionmentioning
confidence: 74%
“…However, in a subgroup of a preselected population at risk of IC, the predictive positive value of the test increased. Two studies involving patients with sepsis and fungal colonization reported that a negative BDG could avoid the initiation of an antifungal treatment without increasing the risk of IFI and death [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic criteria of IC, the proportion of candidemia versus non-candidemic IC, and most importantly, the targeted population of BDG testing and prevalence of the disease could influence diagnostic performances. In the present study, the PPV of BDG for IC diagnosis was 37% for a prevalence of IC of 12% [ 1 ]. We observed comparable results in a study reporting our experience of BDG testing in ICU (PPV 36%, IC prevalence 19%) [ 4 ].…”
mentioning
confidence: 85%
“…To the Editor: De Pascale et al recently reported on the potential role of (1,3)-β- d -glucan (BDG)-guided strategy as an antifungal stewardship tool in patients with sepsis/septic shock and risk factors for invasive candidiasis (IC) [ 1 ]. This raises the question of the possible drawback of false-positive results, which may lead to antifungal treatment (AF) overconsumption.…”
mentioning
confidence: 99%